马来西亚相声本土化初探 = An investigation of localization of Malaysian crosstalk (Xiangsheng) - 李燕淇 Lee, Yen Chie (2010)
相声于清末时期在北京发迹，形成一门幽默讽刺的说唱艺术。从朱绍文开始，相声成为一门行业，盛行于北京天桥。到二十世纪中叶，相声往海外扩展，在台湾、新加坡和马来西亚萌芽，渐渐发展成具有当地特色的说唱艺术。本论文把重点聚焦在马来西亚的相声，主要探讨马来西亚相声后期的发展和马来西亚相声段子的本土化。Xiangsheng (commonly known as “Crosstalk” in English) is a Chinese folk art performance originated in Beijing, China during the late Qing Dynasty. In the middle of the 20th century, Xiangsheng emerged in Taiwan, Singapore, Malaysia and other South-east Asian regions. Over the years, Xiangsheng flourished in these different places outside of China and established its own local characteristics. This thesis focuses on the Malaysian Xiangsheng by examining its development and the features of localization of selected Xiangsheng texts written and performed by local artists. Chapter Two outlines the historical background of Xiangsheng and discusses how it was formed from different rudimentary structures. Chapter Three examines the development of Xiangsheng in Malaysia, and focuses mainly on the later part of the development, namely, from 1997 to 2009. In Chapter Four, several Malaysian Xiangsheng texts are analyzed to highlight how localization of Malaysian Xiangsheng took place. I have also included a chronicle of Xiangsheng events in Malaysia in the Appendix. Important texts of Malaysia Xiangsheng I have acquired during the course of this study, and have used for the writing of this thesis, are also included.